Optical and surface properties of Schiff base ligands and Cu(II) and Co(II) complexes - Alaa Adnan Rashad; Dina A. Najeeb; Shaymaa M. Mahmoud; Evon Akram; Khalid Zainulabdeen; Salam Dulaim; Rahimi M. Yusop (Тонкие химические технологии, 2024)
Objectives. To study the transition of electrons in 1,2-phenyl(4’-carboxy)benzylidene Schiff base ligand and transition metal ions, optical properties, as well as the surface chemistry of supported transition metals using diffuse reflectance spectroscopy (DRS); to study the roughness and morphology of the Schiff base ligand and its complexes using atomic force microscopy (AFM).Methods. DRS, AFM, and Fourier-transform infrared spectroscopy instruments were used to identify electron transitions, optical properties, and surface morphology in Schiff base ligands and their complexes.Results. The DRS revealed the d–d transitions and charge transfer shifts of all compounds, and helped identify the structure of the ligand. One of the optical properties studied was the energy gap calculation of the ligand and its complexes. The copper complex exhibited more semiconducting behavior with surface morphology properties such as surface roughness parameters lower than those of the ligand and the cobalt complex. This can be attributed to the smaller size of the copper atom, as well as lower electron transitions compared to the cobalt complex and the square planar bonding shape.Conclusions. In Schiff base ligands, the reflectance spectrum bands reveal three electron transitions: n→π*, π→π*, and σ→σ* transitions. In cobalt complexes, four transitions are indicated: 4A2(F)→4T1(F), 4A2(F)→4T1(P), charge transfer bands, and tetrahedral geometry. Copper complexes exhibit three transitions: 2B1g→2A1g, 2B1g→2Eg, and charge transfer bands, with a square planar geometry for their structure. The energy gap calculations were 2.42, 2.29, and 2.30 eV, respectively. In the case of the SH ligands, copper complexes, and cobalt complexes, all compounds exhibited semiconductor properties. However, the complexes displayed increased conductivity due to the influence of the metal and coordination structure.